Antibiotic Resistance Genes and Bacterial Communities of Farmed Rainbow Trout Fillets (Oncorhynchus mykiss) - Helsens, Nicolas; Calvez, Ségolène; Prevost, Hervé; Bouju-Albert, Agnès; Maillet, Aurélien; Rossero, Albert; Hurtaud-Pessel, Dominique; Zagorec, Monique; Magras, Catherine (Frontiers in Microbiology, 2020)
The rise of antibiotic resistance is not only a challenge for human and animal health treatments, but is also posing the risk of spreading among bacterial populations in foodstuffs. Farmed fish-related foodstuffs, the food of animal origin most consumed worldwide, are suspected to be a reservoir of antibiotic resistance genes and resistant bacterial hazards. However, scant research has been devoted to the possible sources of diversity in fresh fillet bacterial ecosystems (farm environment including rivers and practices, and factory environment). In this study bacterial communities and the antibiotic resistance genes of fresh rainbow trout fillet were described using amplicon sequencing of the V3-V4 region of the 16S rRNA gene and high-throughput qPCR assay. The antibiotic residues were quantified using liquid chromatography/mass spectrometry methods. A total of 56 fillets (composed of muscle and skin tissue) from fish raised on two farms on the same river were collected and processed under either factory or laboratory sterile filleting conditions. We observed a core-bacterial community profile on the fresh rainbow trout fillets, but the processing conditions of the fillets has a great influence on their mean bacterial load (3.38 ± 1.01 log CFU/g vs 2.29 ± 0.72 log CFU/g) and on the inter-individual diversity of the bacterial community. The bacterial communities were dominated by Gamma- and Alpha-proteobacteria, Bacteroidetes, Firmicutes, and Actinobacteria. The most prevalent genera were Pseudomonas, Escherichia-Shigella, Chryseobacterium, and Carnobacterium. Of the 73 antibiotic residues searched, only oxytetracycline residues were detected in 13/56 fillets, all below the European Union maximum residue limit (6.40 to 40.20 µg/kg). Of the 248 antibiotic resistance genes searched, 17 were found to be present in at least 20% of the fish population (tetracycline resistance genes tetM and tetV, -lactam resistance genes blaDHA and blaACC, macrolide resistance gene mphA, vancomycin resistance genes vanTG and vanWG and multidrug-resistance genes mdtE, mexF, vgaB and msrA) at relatively low abundances calculated proportionally to the 16S rRNA gene.